New pesticides regulation: potential economic impacts of the withdrawal of Pendimethalin in horticultural crops - Garcia-German, Sol; Bardaji, Isabel; Garrido, Alberto (Spanish Journal of Agricultural Research, 2014)
The Thematic Strategy on the Sustainable Use of Pesticides moves forward towards the sustainability of agriculture fostering the use of Integrated Pest Management (IPM) practices in the European Union (EU). EC Regulation 1107/2009 was adopted in this framework leading to the eventual drop in the Vademecum of authorized substances of some important pesticides which are presently used in EU agriculture. Herbicide Pendimethalin will have to renew its registration in 2016 under the new regulation and there is a high probability that it will be removed. In this study we analyze the potential impact of the prohibition of Pendimethalin in two export driven horticultural crops grown in Southeastern Spain - lettuce and celery - to provide an illustration of possible consequences of the loss of certain active substances due to the new regulation. To do so, gross margin stochastic models are developed and used to generate Monte-Carlo simulations to look at farms’ economic results and their production risks. Econometric models are used to examine consumers’ and producers’ surplus in export markets of lettuce and celery. The results show that the Pendimethalin ban might modify the economic risk profile that the farm faces, affecting the crops’ profitability in the short-term. These changes would pass on to markets through shifts in supply and price and finally to European consumers, who would be the major losers.